(untitled) (ModaPalavra e-periódico, 2008)
In this article is proposed a reflection about a paradigm which was established in the XXI century: ‘the sustainable environmental development’ and the implication of that in the creation of clothing products. The costumers, the industry, the creator of new product, all of them have determinant roles in the consolidation of this paradigm. The environmental impacts must be considered in all the steps of the project of new product, from the origin of the raw material to the discard by the costumers. The sustainable development is a big challenge for the creation of new products, and the appeal for consumerism represents a barrier. Observing this context, are identified new scenarios for fashion.